Наземные моллюски (Gastropoda, Pulmonata) заказника Переладино (Подольская возвышенность) - Байдашников, А.А. (Вестник зоологии, 2000)
Обнаружены виды, характерные для Карпат и очень редкие на Подольской возвышенности, в том числе Columella columella (G. Mart.) и Vestia gulo (E. Bielz). Рассмотрены условия их обитания. Within the reservate species characteristic for the Carpathians and very rare for the Podolian Hills, including Columella columella (G. Mart.) and Vestia gulo (E. Bielz), have been found. Habitat conditions of the molluscs are discussed.